1980
DOI: 10.1143/jjap.19.l33
|View full text |Cite
|
Sign up to set email alerts
|

Low Oxygen Content Czochralski Silicon Crystal Growth

Abstract: A low oxygen content silicon crystal ingot with 2.5×1017 to 3.5×1017 atoms·cm-3 was obtained. It was grown by using the Czochralski crystal growth furnace heated with a graphite heater connected to a three phase electrical source, and by controlling the seed and the crucible rotation in conjunction with the fluid rotation caused by the rotating magnetic field of the system. Neither bulk stacking faults after oxidation in wet oxygen at 1100°C for 2 hours, nor oxide precipitates after being annealed in an argon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 0 publications
1
15
2
Order By: Relevance
“…The path is subdivided in coil segments by contact points for supplying out-of-phase alternating current (AC) in delta or star connection. Note, there are few former sporadic ideas to inject immediate steady [16], rotating [17,18] or traveling magnetic fields [19,20] into a silicon melt by such a heatermagnet combination. However, no detailed experimental and analytical results, especially, of the growth of semiconductor compounds have been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…The path is subdivided in coil segments by contact points for supplying out-of-phase alternating current (AC) in delta or star connection. Note, there are few former sporadic ideas to inject immediate steady [16], rotating [17,18] or traveling magnetic fields [19,20] into a silicon melt by such a heatermagnet combination. However, no detailed experimental and analytical results, especially, of the growth of semiconductor compounds have been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…In 1980 Hoshikawa et al [72] and independently Hull [73] reported the first Czochralski silicon crystal growth experiments with such heater-magnet module made of graphite. Rotation rates of 20-30 rpm were observed at the Si melt surface in a 250 mm diameter crucible [72]. Both authors observed an improvement of the oxygen control in the as-grown crystals.…”
Section: The Krist G Mag Solution-a Step To Industrial Scalementioning
confidence: 99%
“…In the late 1970s, workers with large silicon pullers observed systematic anomalies in oxygen content in crystals grown on apparently similar pullers. Specifically it was found that differing oxygen contents could be obtained depending on the sense of the crucible rotation, always with the seed rotating counter to the crucible [114]. Eventually it was discovered that this was due to the rotating magnetic field generated by the three-phase heater elements.…”
Section: Motivationmentioning
confidence: 99%